Applying Video for Writing Descriptive Text in Senior High School in the Covid-19 Pandemic Transition - Maru, Mister Gidion; Nur, Sahril; Lengkoan, Fergina (Universitas Negeri Makassar, 2020)
The emergence of the Covid-19 as the global pandemic with its social and physical distancing consequence has affected educational practices. This paper reports the expereince of carrying out a study on applying youtube video for writing of descriptive text in EFL Class. The purpose of this research was to find out whether the videos can develop studentsâ€™ ability in writing descriptive text or not.Â The study took place in the time before and during the covid-19 emergence. As quantitative research, this study applied pre-experimental design. The participant of this research was the 1st year students of one of the prominence senior high schools in Manado, Indonesia. They were 26 students of language class. The results indicated that the mean score of the post-test is significantly higher that of the pre-test. This points out that the use of YouTube video in teaching the writing of descriptive text is effective. However, the emergence of Covid-19 pandemic influenced the implementation of intervention that later affected studentsâ€™ achievement. The result of this study is not fully in line with the outcome of the previous studies which hypothetically resulted in two to four gains of scores. In addition, it implies that the use of YouTube video in this pandemic transition period seems to be helpful mostly to low level students as they displayed higher gains. Besides, this study denotes the challenges for teachers and students in the Covid-19 pandemic era namely the competence in online learning, and the internet connectivity access and learning mode system.